Formulation of Medium Viscosity Chitosan-Pectin –MJ Protein Nanoparticles Conjugated with Anti-Ep-CAM and Its Cytotoxicity Against T47D Breast Cancer Cell Lines - Anggun Feranisa; Dewa Ayu Arimurni; Hilda Ismail; Ronny Martien; S. Sismindari (Universitas Gadjah Mada, 2015)
Chitosan nanoparticle could become potential formula to protect protein degradation during therapy,since chitosan nanoparticles have “proton sponge hypothesis” mechanism on its protection. Chitosan and pectinis used as basic formula of drug delivery because of its biodegradable and biocompatible properties. Chitosanpectin nanoparticles can be formulated by polyelectrolit complex. EpCAM showed excessive expression inepithelial cancer cells thus can be used as a therapeutic biomarker. MJ protein, a Ribosome-Inactivating Proteins(RIPs) isolated from Mirabilis jalapa L had a higher cytotoxicity on malignant cells than normal cells. MJ proteinneed to be formulated to protect from proteosome degradation in endosome. The aim of this research was todevelop MJ protein-chitosan-pectin nanoparticles and conjugated with anti EpCAM for breast cancer therapy.Mj protein was extracted from M.jalapa leaves. RIPs activity was assayed by supercoiled DNA cleavage. MJprotein were loaded into chitosan nanoparticles using medium viscous chitosan and pectin as cross-linker withpolyelectrolit complex method. Anti EpCAM was conjugated to MJ protein-chitosan-pectin nanoparticles bycarbodiimide reaction and characterized for its entrapment efficiency, morphology by transmission electronmicroscope, particles size, and zeta potential. MJ protein nanoparticles conjugated anti EpCAM and withoutanti EpCAM were cytotoxicity assayed toward T47D and Vero cell lines. MJ protein was able to cleave thesupercoiled DNA into linear and nicked-circular ones. The nanoparticles optimal concentration of mediumviscous chitosan: MJ protein: pectin was 0.01%: 0.01%: 1% (m/v). A high entrapment efficiency of MJ proteinnanoparticles was 98.97 ± 0.07%. Morphology nanoparticles showed an amorphic structure with 200.00 nmparticles size. The nanoparticles conjugated anti EpCAM showed average particles size 367.67nm, polydispersityindex 0.332, and zeta potential +39.97mV. MJ protein-chitosan-pectin nanoparticles conjugated anti EpCAMand unconjugated both had higher cytotoxicity with the IC50 57.64 μg/mL and 46.84 μg/mL respectivelyagainst T47D and 99.38 μg/mL and 111.34 μg/mL against Vero cell lines compared to MJ protein with IC50 of3075.61 μg/mL against T47D and 3286.88 μg/mL against Vero cell lines. Both MJ protein-nanoparticles couldincrease the cytotoxicity effects about 50 times compared to the unformulated MJ protein activity, howeverhad less specificity toward T47D and Vero cell lines.